Threat, hostility and violence in childhood and later psychotic disorder: population-based case–control study. (October 2020) - Morgan, Craig; Gayer-Anderson, Charlotte; Beards, Stephanie; Hubbard, Kathryn; Mondelli, Valeria; Di Forti, Marta; Murray, Robin M.; Pariante, Carmine; Dazzan, Paola; Craig, Thomas J.; Reininghaus, Ulrich; Fisher, Helen L.
Abstract : Background: A growing body of research suggests that childhood adversities are associated with later psychosis, broadly defined. However, there remain several gaps and unanswered questions. Most studies are of low-level psychotic experiences and findings cannot necessarily be extrapolated to psychotic disorders. Further, few studies have examined the effects of more fine-grained dimensions of adversity such as type, timing and severity. Aims: Using detailed data from the Childhood Adversity and Psychosis (CAPsy) study, we sought to address these gaps and examine in detail associations between a range of childhood adversities and psychotic disorder. Method: CAPsy is population-based first-episode psychosis case–control study in the UK. In a sample of 374 cases and 301 controls, we collected extensive data on childhood adversities, in particular household discord, various forms of abuse and bullying, and putative confounders, including family history of psychotic disorder, using validated, semi-structured instruments. Results: We found strong evidence that all forms of childhood adversity were associated with around a two- to fourfold increased odds of psychotic disorder and that exposure to multiple adversities was associated with a linear increase in odds. We further found that severe forms of adversity, i.e. involving threat, hostility and violence, were most strongly associated with increased odds of disorder. More tentatively, we found that some adversities (e.g. bullying, sexual abuse) were more strongly associated with psychotic disorder if first occurrence was in adolescence. Conclusions: Our findings extend previous research on childhood adversity and suggest a degree of specificity for severe adversities involving threat, hostility and violence.